(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
5G efficiently uses technologies like network slicing (NS), network function virtualization (NFV), software-defined network (SDN), and multi-access edge computing (MEC). At the same time, embracing these technologies and creating new services opens the network to a new set of security challenges. This paper presents a threat analysis of MEC features. The paper’s novelty resides in viewing MEC as common ground for the telco and IT sectors. This paper studies the measures according to ISO/IEC 27001:2022 controls. ISO/IEC 27001 is the most popular standard for information security management systems, with a new version published in 2022.